Responsivitas Penyelenggaraan Pelayanan Publik Di Dinas Kependudukan Dan Catatan Sipil Kabupaten Bone - Ramadani, Riski; Mahsyar, Abdul; Rasdiana, Rasdiana (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study  aimed to explain the responsiveness of the implementation of public services at the Department of Population and Civil Registry of Bone Regency. This study used a qualitative method. The research data were collected by means of participant observation, in-depth interviews and documentation studies. The results of this study showed that the ability to respond to the community was good, it was seen from the use of the Head of Service's mobile number as a public number, the speed of service was not good due to the usual network errors and less government apparatus compared to many people, the accuracy of serving was good in accordance with standard operating procedures(SOP), Accuracy in serving was good because it was electronically based, timeliness of service, namely processing time until verification must be on schedule, ability to respond the complaints was  good because it had received complaints and filled out Google Forms implemented by the Regency Population and Civil Registry Office. Keywords: Responsiveness, Public Service